2012
DOI: 10.1163/193724011x615578
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite Profiles in Starved Diporeia spp. Using Liquid Chromatography-Mass Spectrometry (LC-MS) Based Metabolomics

Abstract: A B S T R A C TThe holarctic amphipod Diporeia spp. was historically the most abundant benthic macroinvertebrate in the offshore region of the Laurentian Great Lakes basin. However, since the 1990's, the numbers of Diporeia have declined precipitously throughout the region. Competition for food with introduced dreissenid mussels may be partly to blame for this decline. Thus, a better understanding of how Diporeia responds and adjust to starvation is needed. For this purpose, we used liquid chromatography (LC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 83 publications
2
26
0
Order By: Relevance
“…Zooplankton are DHA-limited in the detritivorous pathway throughout the parameter domain (Figure 3A). Recent work has shown that a range of aquatic invertebrates, including marine zooplankton, catabolize essential PUFAs at high rates (Mezek et al, 2010; Mayor et al, 2011, 2015; Maity et al, 2012) in which case our default zooplankton NPE for DHA of 0.9 (Anderson and Pond, 2000; Mayor et al, 2009) may be too high. Reducing the value of this parameter results in a proportional lowering of predicted zooplankton growth, to the extent that the detritivorous pathway becomes an inferior source of nutrition relative to the microbial pathway (in areas of the plane shown in Figure 3A that are lower than those of the corresponding parameter space shown in Figure 3B).…”
Section: Resultsmentioning
confidence: 94%
“…Zooplankton are DHA-limited in the detritivorous pathway throughout the parameter domain (Figure 3A). Recent work has shown that a range of aquatic invertebrates, including marine zooplankton, catabolize essential PUFAs at high rates (Mezek et al, 2010; Mayor et al, 2011, 2015; Maity et al, 2012) in which case our default zooplankton NPE for DHA of 0.9 (Anderson and Pond, 2000; Mayor et al, 2009) may be too high. Reducing the value of this parameter results in a proportional lowering of predicted zooplankton growth, to the extent that the detritivorous pathway becomes an inferior source of nutrition relative to the microbial pathway (in areas of the plane shown in Figure 3A that are lower than those of the corresponding parameter space shown in Figure 3B).…”
Section: Resultsmentioning
confidence: 94%
“…Increasing in LysoPC could be connected with the lower nutritional value of M. subterranean 848/1 and the attempt to produce energy by polar lipid catabolism in the juvenile mussels. The catabolism of phospholipids was also observed on starved amphipods [97] and on crab larvae approaching metamorphosis [98].…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported the presence of 1-I2MU in Diporeia that were starved for 60 d (Maity et al 2012b). 1-I2MU levels ranged widely across individuals and decreased during our starvation trials.…”
Section: Diatom Feeding Experimentsmentioning
confidence: 95%
“…Metabolomics data from whole organisms were collected using a combination of mass spectrometry coupled with two-dimensional gas chromatography (GCXGC) and liquid chromatography (LC) following protocols described by Maity et al (2012aMaity et al ( , 2012b and Ralston-Hooper et al (2008) with some modifications. Briefly, each sample (composed of a single Diporeia, 0.0021-0.0098 g) was homogenized, methanol (300 mL) and chloroform (450 mL) were added, and the sample was centrifuged in order to separate polar (methanol : water) and nonpolar (chloroform) phases.…”
Section: Metabolomic Analysesmentioning
confidence: 99%
See 1 more Smart Citation